Daya Saing Biji Pala Indonesia di Pasar Internasional - Lina Samhina; Rita Nurmalina; Netti Tinaprilla (Institut Pertanian Bogor, 2023)
Indonesia is a nutmeg exporter with the highest export value during 2012‒2020. However, the growth of Indonesia's export value is lower than its competitors. Therefore, to maintain its position as a major exporter, it is important to know its competitiveness. This study aims to explain the competitiveness of Indonesian nutmeg in the world and in ten export destinations. In addition, this study was conducted to analyze the competitive position in the export destination market. The study uses secondary data from UN Comtrade. The data are Indonesian export values of whole and powdered nutmeg in the international market and in ten destination countries during 2012‒2020. The data were processed using revealed comparative advantage (RCA) and dynamic revealed comparative advantage (DRCA) analysis. The results showed that Indonesian whole and powdered nutmeg were competitive in the world market. However, the competitiveness is lower than nutmeg competitiveness of Sri Lanka. Indonesian nutmegs in ten destination markets are also competitive, with the highest competitiveness being in Italy and Germany. Nevertheless, the always positive growth of competitiveness from two products occurred in Japan, thus make Japan's competitive position in rising star during the period of 2018‒2020. Increasing the competitiveness of nutmeg can be done by increasing the export value of the product through regulations by the government regarding post-harvest handling so that there is only a small amount of aflatoxin. In addition, the government can more focus on increasing exports to Japan. Keywords: competitiveness, dynamic revealed comparative advantage, revealed comparative advantage, nutmeg